Hubungan Pengetahuan dan Sikap Masyarakat tentang Penyakit Demam Berdarah Dengue (DBD) dengan Tindakan Pencegahan DBD di Wilayah Kerja UPTD Puskesmas Rami - Nasution, Dian Permata; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Ginting, Isaharpika Br; Arianti, Imelda Putri (Jurnal Riset Hesti Medan, 2025)
Dengue Hemorrhagic Fever is an infectious disease caused by dengue virus that is transmitted by female mosquitoes from the species Aedes aegypti and Aedes albopictus. Asia Pacific bears 75% of the burden of dengue in the world between 2004 and 2010, while Indonesia is reported as the 2nd country with the largest dengue cases among 30 endemic regions. This study uses the Analytical Survey method, using a cross sectional study design and was carried out in Winangun I Village, Malalayang District. The population in this study were all households in Winangun I Village, Malalayang District, as many as 2085 households, with a sample of 100 respondents. This study uses a questionnaire, and data processing using SPSS. The results showed a significant relationship between knowledge (0.042) and attitude (p = 0.001) with DHF prevention measures in Winangun I Village, Malalayang District. Knowledge and attitude of the community are related to the prevention of dengue hemorrhagic fever in Winangun I Village, Malalayang District. It is hoped that the community can be more active in taking precautions with 3M and the Eradication of Mosquito Nest.